Lithium-sulfur battery interlayer, preparation method and application thereof, and lithium-sulfur battery

The interlayer of lithium sulfur battery prepared by electrospinning and selenization treatment solves the problems of complex preparation and insufficient electrochemical performance in the prior art, and achieves the improvement of specific capacity, magnification and cyclic stability of lithium sulfur batteries.

CN119695308APending Publication Date: 2025-03-25INNER MONGOLIA UNIV FOR THE NATITIES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411868510.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The preparation method of existing lithium-sulfur battery interlayers is complex and has insufficient electrochemical performance, which has problems such as shuttle effect, slow sulfur conversion kinetics and easy lithium dendrites growth.

Method used

By mixing niobium salt, organic carbon source and organic solvent, electrospinning is performed to obtain niobium carbon nanofibers, mixed with selenium powder, carbonization and selenization are successively carried out to prepare a lithium sulfur battery interlayer.

Benefits of technology

This method simplifies the preparation process of lithium-sulfur battery interlayers, and the formed interlayers have excellent electrochemical properties and can effectively improve the specific capacity, magnification and cycling stability of lithium-sulfur battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695308A_ABST
    Figure CN119695308A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium-sulfur battery functional materials, and provides a lithium-sulfur battery interlayer, a preparation method and application thereof, and a lithium-sulfur battery. Nb-doped niobium carbon nanofibers are formed through electrostatic spinning, selenium powder and the niobium carbon nanofibers are mixed, carbonization and selenylation are sequentially carried out, an organic carbon source is carbonized into a carbon base through carbonization, niobium is converted into NbSe2 through selenylation, and the lithium-sulfur battery interlayer (including carbon nanofibers and NbSe2 constructed on the carbon nanofibers) is formed. On the basis of excellent flexibility and mechanical properties, the carbon nanofibers can effectively catalyze Li / S conversion chemistry and inhibit the growth of lithium dendrites; nbSe2 can increase electrocatalysis and increase chemical active sites, initiate conversion and phase change of long-chain LiPSs, inhibit dissolution and shuttling of polysulfide, effectively adjust uniform deposition and diffusion of metal lithium and inhibit dendritic crystal growth. In addition, the preparation method provided by the invention is simple to operate and easy to control.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-sulfur battery functional materials, and in particular to a lithium-sulfur battery interlayer, a preparation method and application thereof, and a lithium-sulfur battery. Background Art

[0002] Lithium-sulfur batteries are secondary batteries with metallic lithium as the negative electrode and sulfur as the positive electrode. They have attracted widespread attention due to their extremely high theoretical capacity and energy density, as well as their environmental friendliness. However, lithium-sulfur batteries also have obvious disadvantages, such as the shuttle effect, slow sulfur conversion kinetics, and easy lithium dendrite growth. In order to overcome the above disadvantages, researchers have proposed a variety of methods such as synthesizing artificial SEI and preparing interlayer materials.

[0003] The related prior art discloses a method for preparing a lithium-sulfur battery interlayer, which comprises first preparing boron-modified carbon fiber, then dispersing flower-like zinc oxide, boron-modified carbon fiber and cellulose nanofibrils in water to obtain a mixed suspension; the mixed suspension is mixed and formed to obtain a wet composite paper; and the wet composite paper is freeze-dried to obtain a lithium-sulfur battery interlayer. However, the preparation method of the boron-modified carbon fiber and the flower-like zinc oxide is cumbersome, making the preparation method of the lithium-sulfur battery interlayer lengthy and complicated. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a lithium-sulfur battery interlayer and its preparation method and application, and a lithium-sulfur battery. The preparation method of the lithium-sulfur battery interlayer provided by the present invention is simple to operate, and the obtained lithium-sulfur battery interlayer has excellent electrochemical properties.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a lithium-sulfur battery interlayer, comprising the following steps:

[0007] The niobium salt, the organic carbon source and the organic solvent are mixed to obtain a spinning solution;

[0008] Electrospinning the spinning solution to obtain niobium carbon nanofibers;

[0009] The niobium carbon nanofibers and selenium powder are mixed, and carbonization and selenization are performed in sequence to obtain the lithium-sulfur battery interlayer.

[0010] Preferably, the niobium salt includes one or more of niobium chloride, niobium nitrate, niobium pentoxide and niobium ethoxide; the organic carbon source includes one or more of polyacrylonitrile, polyvinyl pyrrolidone and polyvinylidene fluoride; and the organic solvent includes one or more of N,N-dimethylformamide, methanol and ethanol.

[0011] Preferably, the mass ratio of the niobium salt to the organic carbon source is 1:0.7-5.

[0012] Preferably, the electrospinning parameters include: injection rate of 0.5-1 mL·h -1 , the positive voltage is 12-18 kV, the negative voltage is 1-3 kV, and the distance between the syringe spinneret and the receiver is 20-25 cm.

[0013] Preferably, the mass ratio of the niobium carbon nanofibers to the selenium powder is 1:2-5.

[0014] Preferably, the carbonization temperature is 200-300° C., the time is 1-3 hours, and the carbonization is carried out under a protective atmosphere.

[0015] Preferably, the temperature of the selenization is 500-1000° C., the time is 1-3 hours, and the selenization is performed under a protective atmosphere.

[0016] The present invention also provides a lithium-sulfur battery interlayer prepared by the preparation method described in the above technical solution.

[0017] The present invention also provides application of the lithium-sulfur battery interlayer described in the above technical solution in a lithium-sulfur battery.

[0018] The present invention also provides a lithium-sulfur battery, comprising a positive electrode, a negative electrode, a separator and an interlayer, wherein the interlayer is the lithium-sulfur battery interlayer described in the above technical solution.

[0019] The invention provides a method for preparing a lithium-sulfur battery interlayer.

[0020] The electrospinning of the present invention can form Nb-doped niobium carbon nanofibers, and the niobium carbon nanofibers have good flexibility and mechanical properties; the selenium powder and the niobium carbon nanofibers are mixed, and carbonization and selenization are performed in sequence, and the carbonization can carbonize the organic carbon source in the niobium carbon nanofibers into a niobium-doped carbon base, and then selenization is performed to convert the niobium doped in the carbon base into NbSe 2 , forming a lithium-sulfur battery interlayer, the lithium-sulfur battery interlayer comprising nano-carbon fibers, and NbSe constructed on the nano-carbon fibers 2 . Nanocarbon fibers can effectively catalyze Li / S conversion and inhibit the growth of lithium dendrites; NbSe 2 It has high conductivity, facilitates electron / ion transport, catalyzes sulfur conversion, and enhances the redox kinetics of lithium polysulfides; NbSe 2 It can increase electrocatalysis and chemical active sites, trigger the transformation and phase change of long-chain LiPSs, inhibit the dissolution and shuttle of polysulfides, effectively regulate the uniform deposition and diffusion of metallic lithium, and inhibit the growth of dendrites. The lithium-sulfur battery interlayer of the present invention combines nanocarbon fibers and NbSe 2 The advantages of the present invention can effectively improve the specific capacity, rate and cycle stability of lithium-sulfur batteries. In addition, the preparation method provided by the present invention is simple to operate and easy to control. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 NbSe obtained in Example 1 2 XRD pattern of @CNF;

[0022] Figure 2 Cyclic voltammetry (CV) curves of lithium-sulfur batteries in the experimental group and the control group;

[0023] Figure 3 Nyquist impedance diagram (EIS) of lithium-sulfur batteries in the experimental group and the control group;

[0024] Figure 4 The constant current discharge / charge curves of the lithium-sulfur batteries in the experimental group and the control group under 0.2C conditions;

[0025] Figure 5 The rate diagram of lithium-sulfur batteries in the experimental group and the control group;

[0026] Figure 6 This is the charge and discharge curve of the experimental group lithium-sulfur battery. DETAILED DESCRIPTION

[0027] The present invention provides a method for preparing a lithium-sulfur battery interlayer, comprising the following steps:

[0028] The niobium salt, the organic carbon source and the organic solvent are mixed to obtain a spinning solution;

[0029] Electrospinning the spinning solution to obtain niobium carbon nanofibers;

[0030] The niobium carbon nanofibers and selenium powder are mixed, and carbonization and selenization are performed in sequence to obtain the lithium-sulfur battery interlayer.

[0031] Unless otherwise specified, the raw materials used in the present invention are preferably commercially available products.

[0032] The invention mixes niobium salt, organic carbon source and organic solvent to obtain spinning solution.

[0033] In the present invention, the niobium salt preferably includes one or more of niobium chloride, niobium nitrate, niobium pentoxide and niobium ethoxide, and more preferably niobium chloride (NbCl 5 ). In the present invention, the organic carbon source preferably includes one or more of polyacrylonitrile, polyvinyl pyrrolidone and polyvinylidene fluoride, and more preferably polyacrylonitrile. In the present invention, the organic solvent preferably includes one or more of N,N-dimethylformamide, methanol and ethanol, and more preferably N,N-dimethylformamide.

[0034] In the present invention, the mass ratio of the niobium salt to the organic carbon source is preferably 1:0.7-5, more preferably 1:0.7-0.9, and specifically preferably 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.2, 1:1.5, 1:1.8, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5 or 1:5. In the present invention, the amount ratio of the niobium salt to the organic solvent is preferably 1g:5-40mL, specifically preferably 1g:5mL, 1g:8mL, 1g:9mL, 1g:10mL, 1g:15mL, 1g:20mL, 1g:25mL, 1g:30mL, 1g:35mL or 1g:40mL.

[0035] In the present invention, the mixing of the niobium salt, the organic carbon source and the organic solvent is preferably carried out under stirring, the stirring temperature is preferably room temperature, the time is preferably 5 to 10 hours, more preferably 8 hours, specifically preferably 5 hours, 6 hours, 7 hours, 8 hours, 9 hours or 10 hours.

[0036] In the present invention, the spinning solution is preferably an orange-yellow transparent solution.

[0037] After obtaining the spinning solution, the present invention performs electrostatic spinning on the spinning solution to obtain niobium carbon nanofibers.

[0038] In the present invention, the electrospinning parameters include: the injection rate is preferably 0.5 to 1 mL·h -1 , more preferably 0.6 to 0.9 mL·h -1 , preferably 0.5 mL·h -1 、0.6mL·h -1 , 0.7 mL·h -1 、0.8mL·h -1 、0.9mL·h -1 or 1mL·h -1 The positive voltage is preferably 12-18 kV, more preferably 13-17 kV, and more preferably 12 kV, 13 kV, 14 kV, 15 kV, 16 kV, 17 kV or 18 kV; the negative voltage is preferably 1-3 kV, and more preferably 1 kV, 2 kV or 3 kV; the distance between the syringe spinneret and the receiver is preferably 20-25 cm. In the present invention, the receiver is preferably a rotating aluminum foil.

[0039] In the present invention, the niobium carbon nanofiber is preferably in a film shape, and the thickness of the film is preferably 0.025 to 0.25 mm.

[0040] After obtaining the niobium carbon nanofibers, the present invention mixes the niobium carbon nanofibers with selenium powder, and sequentially performs carbonization and selenization to obtain the lithium-sulfur battery interlayer.

[0041] In the present invention, the mass ratio of the niobium carbon nanofibers to the selenium powder is preferably 1:2-5, more preferably 1:3-4, and particularly preferably 1:2, 1:3, 1:4 or 1:5.

[0042] In the present invention, the carbonization temperature is preferably 200-300°C, further preferably 220-280°C, specifically preferably 200°C, 220°C, 240°C, 250°C, 260°C, 280°C or 300°C; the time is preferably 1-3h, and the carbonization is preferably carried out under a protective atmosphere, the protective atmosphere is preferably a mixture of hydrogen and argon, the volume ratio of hydrogen and argon in the hydrogen and argon mixture is preferably 1:9-1:19, that is, the volume content of hydrogen in the hydrogen and argon mixture is preferably 5%-10%. In the present invention, the heating rate to the carbonization temperature is preferably 1-5°C / min. After the carbonization, the present invention preferably also includes natural cooling to room temperature. In the present invention, the carbonization can carbonize the organic carbon source in the niobium carbon nanofiber into a niobium-doped carbon base.

[0043] In the present invention, the temperature of the selenization is preferably 500-1000°C, further preferably 600-900°C, more preferably 700-800°C, specifically preferably 600°C, 650°C, 700°C, 750°C, 800°C, 850°C or 900°C; the time is preferably 1-3h, and the selenization is preferably carried out under a protective atmosphere, and the protective atmosphere is preferably a mixture of hydrogen and argon. The volume ratio of hydrogen and argon in the hydrogen and argon mixture is preferably 1:9-1:19, that is, the volume content of hydrogen in the hydrogen and argon mixture is preferably 5%-10%. In the present invention, the heating rate to the temperature of the selenization is preferably 1-5°C / min. After the selenization, the present invention preferably also includes natural cooling to room temperature. In the present invention, the selenization can convert the niobium doped in the carbon base into NbSe 2 .

[0044] The present invention also provides a lithium-sulfur battery interlayer prepared by the preparation method described in the above technical solution. In the present invention, the lithium-sulfur battery interlayer preferably comprises nano-carbon fibers and NbSe constructed on the nano-carbon fibers. 2 In the present invention, the thickness of the lithium-sulfur battery interlayer is preferably 0.025 to 0.25 mm. In the present invention, the nano-carbon fiber can effectively catalyze the Li / S conversion chemistry and inhibit the growth of lithium dendrites; NbSe 2 It can increase electrocatalysis and chemical active sites, trigger the transformation and phase change of long-chain LiPSs, inhibit the dissolution and shuttle of polysulfides, effectively regulate the uniform deposition and diffusion of metallic lithium, and inhibit the growth of dendrites. The lithium-sulfur battery interlayer of the present invention combines nanocarbon fibers and NbSe 2The advantages of the present invention can effectively improve the specific capacity, rate and cycle stability of lithium-sulfur batteries. In addition, the preparation method provided by the present invention is simple to operate and easy to control.

[0045] The present invention also provides application of the lithium-sulfur battery interlayer described in the above technical solution in a lithium-sulfur battery.

[0046] The present invention also provides a lithium-sulfur battery, comprising a positive electrode, a negative electrode, a separator and an interlayer, wherein the interlayer is the lithium-sulfur battery interlayer described in the above technical solution.

[0047] In the present invention, the negative electrode is preferably a lithium sheet, and the positive electrode is preferably sulfur. The present invention does not specifically limit the material of the separator, and a separator of a lithium-sulfur battery well known to those skilled in the art can be used. In the present invention, the interlayer is preferably placed between the positive electrode and the separator.

[0048] The lithium-sulfur battery interlayer, preparation method and application thereof, and lithium-sulfur battery provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0049] Example 1

[0050] 1 g of niobium pentachloride and 0.9 g of polyacrylonitrile were added to 9 mL of N,N-dimethylformamide, the beaker was sealed with a sealing film, and a uniform orange-yellow spinning solution was formed after stirring at room temperature for 8 h. -1 Electrospinning was performed at a constant injection speed and with a positive voltage of 17 kV and a negative voltage of 3 kV applied. The distance between the syringe spinneret and the receiver was 20 cm, and the niobium carbon nanofibers were received on a rotating aluminum foil.

[0051] The niobium carbon nanofibers and selenium powder prepared above were mixed in a mass ratio of 1:3, heated from room temperature to 250°C at a heating rate of 1°C / min, and carbonized for 2 hours in a hydrogen-argon atmosphere (the volume ratio of hydrogen to argon was 1:9). After the carbonization, the mixture was naturally cooled to room temperature, and then heated from room temperature to 600°C at a heating rate of 5°C / min, and selenized for 2 hours in a hydrogen-argon atmosphere (the volume ratio of hydrogen to argon was 1:9). After the selenization, the mixture was naturally cooled to room temperature to obtain a flexible and self-supporting lithium-sulfur battery interlayer, denoted as NbSe 2 @CNF, thickness is 0.025~0.25mm.

[0052] Performance Testing

[0053] (1) Physical property parameter test

[0054] In order to obtain the obtained NbSe 2 @CNF chemical composition information, NbSe 2@CNF conducted an XRD test and the results are as follows Figure 1 As shown, Figure 1 The obtained NbSe 2 XRD pattern of @CNF, from Figure 1 It can be seen that: NbSe 2 The diffraction peaks of @CNF and NbSe 2 Standard crystal card PDF: 87-2415 completely corresponds, indicating that the prepared material is NbSe 2 @CNF Materials.

[0055] (2) Electrochemical performance test

[0056] With SuperP / S electrode as the positive electrode, NbSe 2 @CNF material was used as an independent self-supporting interlayer, placed between the positive electrode and the separator, and lithium metal was used as the negative electrode to assemble a lithium-sulfur battery. As the experimental group, it was recorded as SP-NS@MR. At the same time, a lithium-sulfur battery was assembled using SuperP / S electrode as the positive electrode and lithium metal as the negative electrode without setting an interlayer. It was recorded as the control group, recorded as SP.

[0057] (2.1) Cyclic voltammetry test

[0058] The experimental group and the control group lithium-sulfur batteries were subjected to cyclic voltammetry tests. The results are as follows Figure 2 As shown, Figure 2 The cyclic voltammetry (CV) curves of the experimental and control lithium-sulfur batteries are shown in Figure 2. Figure 2 a is the lithium-sulfur battery of the experimental group and the control group at 0.1mV·s -1 Cyclic voltammetry curves at sweep rate, Figure 2 b is the experimental group of lithium-sulfur batteries at 0.2mV·s -1 ~1.2mV·s -1 Cyclic voltammetry curves at the sweep rate. Figure 2 It can be seen that using NbSe 2 The experimental group of lithium-sulfur batteries with CNF materials as independent self-supporting interlayers showed two oxidation peaks of 2.30V and 2.40V, and reduction peaks of 2.33V and 2.03V. The measured CV curves were consistent with the typical redox reactions of lithium-sulfur batteries. Figure 2 It can be seen from b that at 0.2mV·s -1 ~1.2mV·s -1 The cyclic voltammetry curves under the sweep rate show that the experimental group lithium-sulfur battery has the smallest potential difference between the oxidation peak and the reduction peak compared with the control group lithium-sulfur battery, indicating that NbSe 2 Nanoparticles are beneficial for Li 2The nucleation and deposition process of S can better suppress electrochemical polarization and improve the chemical reaction kinetics. In addition, the experimental group of lithium-sulfur batteries has a higher peak current, which means that the polysulfide conversion process is easier, indicating that NbSe 2 @CNF has an excellent effect on the catalytic conversion of polysulfides.

[0059] (2.2) AC impedance test

[0060] The experimental group and the control group lithium-sulfur batteries were subjected to AC impedance tests. The results are as follows Figure 3 As shown, Figure 3 Nyquist impedance diagram (EIS) of the experimental group and the control group lithium-sulfur battery. Figure 3 It can be seen that the semicircular charge transfer resistance of the experimental group and the control group lithium-sulfur batteries are 23.83Ω and 44.15Ω respectively. It can be seen that the interface resistance and charge transfer resistance of the control group lithium-sulfur battery are large, while the resistance of the experimental group lithium-sulfur battery is small, which is more conducive to charge transfer and shows good conductivity.

[0061] (2.3) Electrochemical performance test

[0062] The experimental group and the control group lithium-sulfur batteries were subjected to electrochemical tests. The results are as follows Figure 4 As shown, Figure 4 The constant current discharge / charge curves of the experimental group and the control group lithium-sulfur batteries under 0.2C conditions. Figure 4 It can be seen that the specific capacities of the first discharge of the lithium-sulfur batteries in the experimental group and the control group are 1124.6 mAh g -1 and 662.8mAh·g -1 The discharge / charge platform of the experimental group lithium-sulfur battery is significantly longer than that of the control group lithium-sulfur battery, which will lead to a higher battery capacity. At the same time, the polarization △E of the experimental group lithium-sulfur battery is small, proving that NbSe 2 @CNF helps reduce battery polarization and improve the reaction kinetics of lithium-sulfur batteries.

[0063] The rate performance of the experimental group and the control group lithium-sulfur batteries was tested at a current density of 0.1C to 5C. The rate performance of the two lithium-sulfur batteries was studied and analyzed. The results are as follows Figure 5 and Figure 6 As shown, Figure 5 The rate diagram of the lithium-sulfur battery in the experimental group and the control group. Figure 5 It can be seen that at the current densities of 0.1C, 0.5C, and 10C, the first cycle discharge specific capacity of the control group lithium-sulfur battery is 615.1 mAh g -1 、580.32mAh·g -1 and 34.6 mAh g -1The discharge capacity of the experimental group lithium-sulfur batteries was 1217.2 mAh g -1 、979.48mAh·g -1 and 608.2mAh·g -1 When returning to 0.1C stability, the discharge capacities of the control group and experimental group lithium-sulfur batteries were 558.1 mAh g -1 and 1012.9mAh·g -1 By comparison, NbSe 2 @CNF assembled lithium-sulfur batteries have better rate performance, especially at larger discharge currents, and have good reversibility.

[0064] Figure 6 The charge and discharge curve of the experimental group lithium-sulfur battery is shown in Figure 2. Figure 6 It can be seen that when the discharge current density is gradually increased to 5C, the experimental group of lithium-sulfur batteries still has the typical charge and discharge platform of lithium-sulfur batteries, indicating that even at high rates, NbSe 2 @The experimental group of lithium-sulfur batteries assembled by CNF still has good application potential.

[0065] Example 2

[0066] The difference from Example 1 is that the mass of niobium pentachloride is adjusted to 0.9 g, and the rest is the same as Example 1.

[0067] Example 3

[0068] The difference from Example 1 is that the mass of niobium pentachloride is adjusted to 0.45 g, and the rest is the same as Example 1.

[0069] Comparative Example 1

[0070] The difference from Example 1 is that the mass of niobium pentachloride is adjusted to 1.35 g, and the solution cannot be spun.

[0071] Comparative Example 2

[0072] The difference from Example 1 is that the mass of niobium pentachloride is adjusted to 1.8 g. The other conditions are the same as Example 1, and the solution cannot be spun.

[0073] The performance of the lithium-sulfur batteries of Examples 2-3 and Comparative Examples 1-2 was tested using the testing method of Example 1. The results are shown in Table 1.

[0074] Table 1 Performance test results of lithium-sulfur batteries obtained in Examples 2 to 3 and Comparative Examples 1 to 2

[0075]

[0076] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a lithium-sulfur battery interlayer, characterized in that: The following steps are involved: The niobium salt, the organic carbon source and the organic solvent are mixed to obtain a spinning solution; Electrospinning the spinning solution to obtain niobium carbon nanofibers; The niobium carbon nanofibers and selenium powder are mixed, and carbonization and selenization are performed in sequence to obtain the lithium-sulfur battery interlayer.

2. The preparation method according to claim 1, characterized in that: The niobium salt includes one or more of niobium chloride, niobium nitrate, niobium pentoxide and niobium ethoxide; the organic carbon source includes one or more of polyacrylonitrile, polyvinyl pyrrolidone and polyvinylidene fluoride; and the organic solvent includes one or more of N,N-dimethylformamide, methanol and ethanol.

3. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the niobium salt to the organic carbon source is 1:0.7-5.

4. The preparation method according to claim 1, characterized in that: The parameters of the electrospinning include: injection rate of 0.5-1 mL·h -1 , the positive voltage is 12-18 kV, the negative voltage is 1-3 kV, and the distance between the syringe spinneret and the receiver is 20-25 cm.

5. The preparation method according to claim 1, characterized in that: The mass ratio of the niobium carbon nanofiber to the selenium powder is 1:2-5.

6. The preparation method according to claim 1 or 5, characterized in that: The carbonization temperature is 200-300° C., the time is 1-3 hours, and the carbonization is carried out under a protective atmosphere.

7. The preparation method according to claim 1 or 5, characterized in that: The temperature of the selenization is 500-1000° C., the time is 1-3 hours, and the selenization is carried out under a protective atmosphere.

8. A lithium-sulfur battery interlayer prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the lithium-sulfur battery interlayer according to claim 8 in lithium-sulfur batteries.

10. A lithium-sulfur battery, characterized in that: It comprises a positive electrode, a negative electrode, a separator and an interlayer, and the interlayer is the lithium-sulfur battery interlayer as claimed in claim 8.